Women’s Rights in the Qur’an: An Epistemological Re-examination of Theological, Moral, and Social Frameworks - Enok Ghosiyah; Ikhwan Ansori (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2025)
This study aims to reconstruct the epistemology of understanding women in the Qur’an through theological, moral, and social approaches. Historically, interpretations of verses concerning women have been influenced by patriarchal cultural biases, undermining the Qur’an’s universal humanistic values. Employing thematic exegesis (maudhu‘i) and contextual hermeneutics, this research analyzes verses on human creation, spiritual equality, and women’s social roles within the framework of tawhid (divine unity) and justice. The findings reveal that the Qur’an affirms women as moral and spiritual beings with dignity equal to men, grounded in the principles of tawhid, justice (‘adl), and societal welfare (maslahah). These principles serve as a theological foundation for the full humanity of women in both social and moral contexts. The epistemological reconstruction challenges patriarchal interpretations and offers an inclusive, transformative paradigm for Qur’anic gender discourse. By integrating theological rigor with ethical-social analysis, this study contributes to contemporary Islamic scholarship, advocating for gender justice aligned with the Qur’an’s egalitarian ethos. The proposed framework not only reinterprets classical exegesis but also provides a normative basis for equitable gender relations in Muslim societies.